Neuroendocrine tumor of the skin of head and neck - Stošić Srboljub; Đurđević Dejan; Kozomara Ružica; Mirković Zoran; Stošić-Opinćal Tatjana (Vojnosanitetski Pregled)
Background. Merkel cell carcinom is a rare neuroendrocine tumor of skin which manifests it self through aggressive growth and early regional metastasis. It develops mainly in older population. Locally, the tumor spreads intracutaneously. Case report. We showed two cases (females of 89 and 70 years old) hospitalized within the last two years. The first patient was treated surgically three times. After the surgery, the patient was treated with radio therapy, and died 3 years from the beginning of the treatment. The second patient with this neuroendocrine tumor with the high malignancy potential and huge regional metastasis, was treated surgically, and died a month and a half after the operation. Conclusion. These two cases confirmed the aggressive and recidivant growth of this tumor with the difficult pathologic investigation, and the extremely bad prognosis inspite of the treatment.